Lipocalin‐2 ensures host defense against Salmonella Typhimurium by controlling macrophage iron homeostasis and immune response. Issue 11 (30th September 2015) - Nairz, Manfred; Schroll, Andrea; Haschka, David; Dichtl, Stefanie; Sonnweber, Thomas; Theurl, Igor; Theurl, Milan; Lindner, Ewald; Demetz, Egon; Aßhoff, Malte; Bellmann‐Weiler, Rosa; Müller, Raphael; et al.
Abstract : Lipocalin‐2 (Lcn2) is an innate immune peptide with pleiotropic effects. Lcn2 binds iron‐laden bacterial siderophores, chemo‐attracts neutrophils and has immunomodulatory and apoptosis‐regulating effects. In this study, we show that upon infection with Salmonella enterica serovar Typhimurium, Lcn2 promotes iron export from Salmonella ‐infected macrophages, which reduces cellular iron content and enhances the generation of pro‐inflammatory cytokines. Lcn2 represses IL‐10 production while augmenting Nos2, TNF‐α, and IL‐6 expression. Lcn2 −/− macrophages have elevated IL‐10 levels as a consequence of increased iron content. The crucial role of Lcn‐2/IL‐10 interactions was further demonstrated by the greater ability of Lcn2 −/− IL‐10 −/− macrophages and mice to control intracellular Salmonella proliferation in comparison to Lcn2 −/− counterparts. Overexpression of the iron exporter ferroportin‐1 in Lcn2 −/− macrophages represses IL‐10 and restores TNF‐α and IL‐6 production to the levels found in wild‐type macrophages, so that killing and clearance of intracellular Salmonella is promoted. Our observations suggest that Lcn2 promotes host resistance to Salmonella Typhimurium infection by binding bacterial siderophores and suppressing IL‐10 production, and that both functions are linked to its ability to shuttle iron from macrophages.